Sponges in a Changing Climate: Survival of Agelas oroides in a Warming Mediterranean Sea - Idan, Tal; Goren, Liron; Shefer, Sigal; Ilan, Micha (Frontiers in Marine Science, 2020)
Sponges hold a key role in benthic environments, and specifically in the Mediterranean Sea. Past events of mass mortality in sponge communities have been linked to extended periods of high-temperature anomalies, yet it is unknown how a gradual change, such as the constant rise in global seawater temperatures, will affect biodiversity. Here we present a case study of Agelas oroides, a common massive sponge in the Mediterranean Sea, found at a wide depth range of 1-150 m. Last documented in the 1970s, A. oroides was considered lost from the Israeli coastal fauna. However, its recent rediscovery in mesophotic depths, where environmental conditions are stable, provided an opportunity to examine whether it can survive the present conditions in the shallow Israeli coast – where temperatures increased by 3°C during the past 60 years, while the nutrients concentration decreased following the damming of the Nile River. To test this hypothesis, A. oroides individuals were collected during winter from mesophotic sponge grounds (100-120 m) and transplanted to a shallow rocky habitat (10 m). Control individuals were transplanted back to the mesophotic habitat. Sponge survival, temperature, and nutrient concentrations were measured in both habitats. The shallow-transplanted sponges' survival decreased only when the ambient temperature exceeded 28°C. In contrast, the control group at the mesophotic depth, where the temperature never rose above 20°C, survived the duration of the experiment. Our findings suggest that a prolonged period of high temperatures may constitute a major factor in A. oroides survival and disappearance from the Israeli shallow habitats.